Niveles de compost de nabo, en el rendimiento de Lactuca sativa L., lechuga, en la Región Loreto.2023 - Del Aguila Coloma, Claudio Magno (2024)
This abstract focuses on research on the effects of different levels of turnip compost on the agronomic characteristics and yield of lettuce in the Loreto Region. Various treatments were carried out using different levels of turnip compost and different parameters of agronomic characteristics and yield were valued. Among the different treatments evaluated, the T4 treatment with 60 t of compost / ha, showed the best results, where in this treatment a greater growth in height and width of the plant was observed compared to the other treatments; in addition, the T4 also showed a greater weight of root but not in length, which indicates a greater development of the plant in volume of the root system; Likewise, it was observed that this treatment presented a greater number of leaves per plant, which indicates a greater production of leaf biomass. Regarding the weight of the leaves and total weight per plant (204 g) and weight of leaves / ha (30,600 t / ha), the T4 also stood out showing values higher than the other treatments; This indicates that the use of proper turnip compost levels can positively influence lettuce yield in terms of weight and quantity of leaves. In conclusion, the results obtained in this research suggest that T4 with adequate levels of turnip compost can promote better growth and development of lettuce in the Loreto Region. These findings are relevant to agricultural production in the area as they provide useful and practical information that can improve the agronomic characteristics and crop yields of lettuce crops using turnip compost.